The Importance of Public Relations in Corporate Sustainability (Global Journal of Management and Business Research, 2014)
The purpose of this article was to present the importance of using public relations to communicate the intent and application of corporate sustainability by organizations that are involved in this practice. Since there are three areas that corporate sustainability is involved with, corporate/business. The CEOs of organizations responsible for the strategic formulation and application of public relations need to have the appropriate vision in order to merge the target of public relations with the ever-changing internal and external environment of the organization. Public Relations must be embraced by organizations that follow the corporate sustainability model. From an internal/external perspective, stakeholders, employees, and the public must communicate effectively, efficiently, and on a timely basis in order to enhance their positive interaction and attain the desired goals.
Keywords: corporation; social responsibility; sustainability; corporate sustainability; ecology; sociology; ceo; internal environment; external environment; pub